Chemical and Antioxidant Studies of Citrus macroptera (Bangladesh Journal of Scientific and Industrial Research, 2009)
Lupeol (1) and Stigmasterol (2) were isolated from the crude extracts of the stem bark of Citrus macroptera (Family: Rutaceae) for the first time. The n-hexane, dichloromethane and methanol extracts were screened in vitro for antioxidant activity using the 1, 1-diphenyl-2-picrylhydrazyl-hydrate (DPPH) free radical scavenging assay. The hot methanol extract showed potential antioxidant activity (IC50: 178.96 Î¼g/ml) whereas the cold methanol and dichloromethane extracts showed moderate activity (IC50: 242.78 Î¼g/ml and 255.78 Î¼g/ml respectively). Mild antioxidant activity was observed with the n-hexane extract of the stem bark of Citrus macroptera (IC50: 422.94 Î¼g/ml). Key words: Citrus macroptera, Rutaceae, Lupeol, Stigmasterol, Antioxidant. Â  doi: 10.3329/bjsir.v43i4.2235 Bangladesh J. Sci. Ind. Res. 43(4), 449-454, 2008